Dimensional Psychopathology (Springer International Publishing, 2018)
This book presents an innovative approach to clinical assessment in psychiatry based on a number of psychopathological dimensions with a presumed underlying pathophysiology, that are related to fundamental phenomenological aspects and lie on a continuum from normality to pathology. It is described how the evaluation of these dimensions with a specific, validated rapid assessment instrument could easily integrate and enrich the classical diagnostic DSM-5 or ICD-10 assessment. The supplemental use of this dimensional approach can better capture the complexity underlying current categories of mental illness. The findings from a large patient sample suggest how this assessment could give a first glance at how variable and multifaceted the psychopathological components within a single diagnostic category can be, and thereby optimise diagnosis and treatment choices. Being short and easy to complete, this dimensional assessment can be done in a busy clinical setting, during an ordinary psychiatric visit, and in an acute clinical context, with limited effort by a minimally trained clinician. Therefore, it provides interesting and useful information without additional costs, and allows research work to be performed even in difficult settings.